Simultaneous Observations of a Sporadic E Layer by Digisonde and SuperDARN HF Radars at Zhongshan, Antarctica. Issue 2 (22nd February 2022) - Chen, Xiangcai; Liu, Jianjun; Kosch, Michael J.; Hu, Zejun; Wang, Zhiwei; Zhang, Beichen; Yang, Huigen; Hu, Hongqiao
Abstract: Sporadic E ( E s) layers could be composed of metallic ions and formed, modified, or transported by the action of convective electric fields in the high latitude ionosphere. In this paper, by utilizing simultaneous observations from Digisonde and Super Dual Auroral Radar Network (SuperDARN) HF radars at Zhongshan Station (ZHS, 69.4°S, 76.4°E), Antarctica, a thin E s layer, which initially formed in the lower F region and descended into the lower E region, with wavelike structures, was recorded by Digisonde on 14 November 2019. The Es layer‐related concurrent ionospheric irregularities were also detected by the SuperDARN ZHS HF radar. By using a global‐scale 2‐D convection map, combined with images from the Special Sensor Ultraviolet Spectrographic Imager instruments onboard Defense Meteorological Satellite Program (DMSP) spacecraft, it is proposed that the flow shears associated with the duskside convective circulation are responsible for the evolution of the E s layer. Moreover, using the HF radar elevation angle data to measure the scatter height, it is strongly suggested that the Es layer was elongated with convection circulation. The electrodynamic processes responsible for the formation and evolution of the E s layer are discussed. Key Points: An E s layer formed in the lower F region and descended to the E region, observed simultaneously by Digisonde and Super Dual Auroral Radar Network (SuperDARN) HF radars The formation and evolution of the E s layer related to the afternoon convection reversal SuperDARN HF radar measurements suggest the E s layer is elongated with convection circulation